Savings Mobilization Efforts of the Nigerian Money Market and Economic Growth - Caleb Kehinde Osamo; Odi Nwankwo (Britain International for Academic Research (BIAR) Publisher, 2024)
Economic growth is a function of some productive efforts among which savings mobilizations is considered very vital. This study examined saving mobilization efforts of the Nigerian money market and the effects on economic growth during the year 2001 – 2022.Vested with the objectives to investigate the effect of banking density, savings rates and money supply on economic growth. The study relied on time series data sourced from the publication of the Central Bank of Nigeria. Gross Domestic Product Growth Rate (GDPGR) was adopted as dependent variable, while Banking Density (BD), Savings Rates (SR) and Money Supply (MS) were the independent variables. Augmented Dickey Fuller (ADF) unit root test was employed, to test the stationarity. The Auto Regressive Distributive Lag (ADRL) was used to ascertain the relationship between the variables alongside Vector Error Correction Model (VCM). Post estimation diagnostic tools used include; Breuch-Godfrey serial correlation LM test and the CUSUM test for stability. From the ARDL, β-coefficient and the associated probabilities were adopted to determine the extent and direction of relationship on economic growth. Data were tested at 5% level of significance, it was discovered that banking density and savings rates affected economic growth positively but with insignificant effects, while money supply affected economic growth negatively with insignificant effect. The study therefore recommends amongst other, that stakeholders, be directed towards entrenching higher banking density as opposed to banking desert, and that money supply should be made dynamic in accordance with economic realities.